2005
DOI: 10.1590/s0104-56872005000200007
|View full text |Cite
|
Sign up to set email alerts
|

Gravidade do distúrbio fonológico: julgamento perceptivo e porcentagem de consoantes corretas

Abstract: A correlation between the perceptual judgment and the PCC indexes exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
30

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 14 publications
0
21
0
30
Order By: Relevance
“…It should be emphasized that the mean time of daily use of the hearing device was 8.3 hours. In relation to the mean indices (calculated by the average of the three applied tests) obtained individually by the children, the degrees of phonological disorders were classified 6,7 in the evaluation and in the reevaluation. In this analysis, it was observed that 12 children positively modified the degree of phonological disorder between the evaluations, after intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that the mean time of daily use of the hearing device was 8.3 hours. In relation to the mean indices (calculated by the average of the three applied tests) obtained individually by the children, the degrees of phonological disorders were classified 6,7 in the evaluation and in the reevaluation. In this analysis, it was observed that 12 children positively modified the degree of phonological disorder between the evaluations, after intervention.…”
Section: Methodsmentioning
confidence: 99%
“…This measure is part of the classification system of the diagnosis of the phonological disorder, based on an increasing scale of severity 6 . The index of PCC values includes four severities: light, which corresponds to more than 85% of correct consonants; slightly moderate, ranging from 85% to 65%; moderately severe, ranging from 50 to 65%; and severe, indicated by values below 50% of correct consonants 7 .…”
Section: Introductionmentioning
confidence: 99%
“…One might say that the typical phonological acquisition happens when the child sets up a phonological system matching the adult target. In Brazilian Portuguese, this process happens gradually and in a non-linear way between birth and the age of 5:0, according to the individual differences of each child Over the last years, there have been an increasing number of studies on the importance of complementary assessments for an improved PD diagnosis and a more effective therapeutic planning [8][9][10] . One of the advantages of the qualitative assessment was singled out by a study that demonstrated a better description of the repair strategies used by children suffering from PD 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Other researches point out the importance of adopting quantitative measures as a marker of phonological system normalization. Also, the PCC can be used as a control during speech therapy 8,11 . Laboring from this knowledge on qualitative and quantitative assessments used in phonoaudiological research and therapy, this study aimed to check if there are any differences between the severity ratings obtained using the PCC-R 4 and the qualitative assessment based on features 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This measure is one of the components of the diagnostic classification system of phonological disorder (6) . The PCC index establishes four degrees of severity: mild, corresponding to more than 85% correct consonants; mildly moderate, with the proportion of correct consonants ranging from 65% to 85%; moderately severe, ranging from 50 to 65%; and severe, corresponding to less than 50% correct consonants (7) .…”
Section: Introductionmentioning
confidence: 99%